Effect of lycopene administration on plasma glucose, oxidative stress and body weight in streptozotocin diabetic rats - Duzguner, Vesile; Kucukgul, Altug; Erdogan, Suat; Colik, Sefa; Şahin, Kazım (Taylor & Francis Ltd, 2008)
To evaluate the role of lycopene, a carotenoid antioxidant, on streptozotocin (STZ)-induced diabetic rats, 12 female rats received a single intraperitonial injection of STZ at a dose of 45 mg/kg body weight of which 6 were given 10 mg/kg lycopene orally (test group) once daily for 21 days. The administration of STZ caused a significant increase in plasma glucose and decrease in body weight. The supplementation of lycopene significantly reduced diabetic plasma glucose level by 25% and prevented body weight loss starting from 14(th) day of lycopene administration. Although tissue lipid peroxidation and nitric oxide (NO) levels were unchanged, lycopene administration significantly reduced diabetes-elevated lipid peroxidation and NO in plasma. It was concluded that lycopene supplementation may be valuable for correcting hyperglycemia and preventing diabetic complications caused by lipid peroxidation and free radicals.
Keywords: diabetes; lipid peroxidation; lycopene; STZ; rat